2019
DOI: 10.1186/s13059-019-1853-6
|View full text |Cite
|
Sign up to set email alerts
|

EpiMethylTag: simultaneous detection of ATAC-seq or ChIP-seq signals with DNA methylation

Abstract: Activation of regulatory elements is thought to be inversely correlated with DNA methylation levels. However, it is difficult to determine whether DNA methylation is compatible with chromatin accessibility or transcription factor (TF) binding if assays are performed separately. We developed a fast, low-input, low sequencing depth method, EpiMethylTag, that combines ATAC-seq or ChIP-seq (M-ATAC or M-ChIP) with bisulfite conversion, to simultaneously examine accessibility/TF binding and methylation on the same D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…Thus, it is imperative to develop methodologies to dissect the concurrent, dynamic changes of the epigenome (Table 2). Toward this direction, in the last two years we have witnessed the development of techniques that allow the simultaneous detection of alterations in chromatin accessibility and DNA methylation: EpiMethylTag, 131 Methyl‐ATAC‐seq 132 and ATAC‐me 133 . However, changes in chromatin accessibility are frequently associated with changes in 5hmC 18,35,57 .…”
Section: Perspectivesmentioning
confidence: 99%
“…Thus, it is imperative to develop methodologies to dissect the concurrent, dynamic changes of the epigenome (Table 2). Toward this direction, in the last two years we have witnessed the development of techniques that allow the simultaneous detection of alterations in chromatin accessibility and DNA methylation: EpiMethylTag, 131 Methyl‐ATAC‐seq 132 and ATAC‐me 133 . However, changes in chromatin accessibility are frequently associated with changes in 5hmC 18,35,57 .…”
Section: Perspectivesmentioning
confidence: 99%
“…Importantly, when ATAC-Me was applied to THP-1 cells, a cell line derived from a monocytic leukemia, Barnett et al revealed that regions of the genome that are accessible do indeed correspond to underlying regions of the genome that also lack DNA methylation. Importantly, comparable genome-wide approaches (m-ATAC-seq and M-ATAC) based on transposition coupled with bisulfite conversion have also recently been reported (Lhoumaud et al, 2019;Spektor et al, 2019) and similarly conclude that accessible regions of the genome typically lack DNA methylation.…”
mentioning
confidence: 62%
“…Msuite adapts our previous sequencing data preprocessing tool, Ktrim, 26 to perform extra-fast, accurate adapter-/quality-trimming, and in silico cytosine-to-thymine conversion of the sequencing reads. Notably, Msuite supports sequencing data generated from various library preparation kits and is able to directly handle conventional WGBS and emerging sequencing protocols such as TAPS, 15 5hmC-CATCH, 16 and ACE-seq, 17 as well as ATAC-me, 27 methyl-ATAC-seq, 28 and EpiMethylTag 29 (integrative methods that measure DNA methylation at regulatory elements, such as accessible chromatin or transcription factor binding domains). Msuite then aligns the pre-processed reads to the reference genome in either 3- or 4-letter mode based on the assay and users' settings (see Experimental Procedures ).…”
Section: Resultsmentioning
confidence: 99%